La diversidad como problema - Jordi Garreta i Bochaca (Universidad de La Rioja, 2013)
The cultural diversity is one of the lines of definition of our society. In a context, in the one that the diversity -for the migrations- it leaves increasing it is necessary to think about mutual adaptations, beyond the assimilation. The school, reflective institution of the dominant ideologies in this sense, it should take in consideration this diversity and to transform it into wealth more than in a problem. Noticing the experience of the Quebec and other societies that have received during many years immigrants, considers interesting to keep in mind their experience and, for example, to thoroughly revise the school material, to develop the mediator's figure (a professional that it can increase the communication among centre and family, relationship that is influenced by linguistic, socio-economic, cultural and institutional differences); etc.